The suppressive role of GLS in radiosensitivity and irradiation-induced immune response in LUAD: integrating bioinformatics and experimental insights - Peicheng Jiang; Zhifeng Jiang; Su Li; Su Li; Ye-Xiong Li; Yuqiong Chen; Xinyan Li (Frontiers in Immunology)
BackgroundRadiotherapy elicits immune activation, thereby synergistically enhancing systemic tumor control when combined with immunotherapy. Glutaminase (GLS), a key enzyme for glutamine metabolism, has been found to regulate glutamine availability within tumor microenvironment (TME). However, the precise mechanisms through which GLS modulates radiosensitivity and irradiation-induced immune responses in lung adenocarcinoma (LUAD) and its clinical value remain to be fully elucidated.MethodsWe employed bulk RNA-seq and single-cell transcriptomics to explore the role of GLS expression in radiosensitivity and immune infiltration. The bioinformatic results were validated by in vitro and in vivo experiments. Co-culture assays and flow cytometry were used to validate the impact of GLS expression on CD8+ T cell activation and cytotoxicity. Moreover, a GLS-DSBr (double strand break repair) prognostic model was developed using machine learning with data from 2,066 LUAD patients.ResultsIn vitro and in vivo experiments demonstrated that GLS silence inhibited DSB repair and promoted ferroptosis, therefore enhancing radiosensitivity. Single-cell and spatial transcriptomics revealed the immunomodulatory effects of GLS expression in the TME. Further, Co-culture assays and flow cytometry experiments indicated that silencing GLS in LUAD cells potentiated the activation and cytotoxicity of CD8+ T cells in the context of radiotherapy. The GLS-DSBr model demonstrated robust predictive performance for overall survival, as well as the efficacy of radiotherapy and immunotherapy in LUAD. The applicability of GLS-DSBr model was further validated through pan-cancer analysis.ConclusionIn the contexts of radiotherapy, GLS downregulation exerts dual regulatory effects by modulating ferroptosis and remodeling the immune landscapes, particularly enhancing CD8+ T cell cytotoxicity. Our work suggests that strategies preferentially targeting GLS in tumor cells may represent promising and translatable therapeutic approaches to promote antitumor efficacy of radiotherapy plus immune checkpoint blockade in LUAD patients. Furthermore, the established GLS-DSBr model serves as a robust predictive tool for prognosis and effects of radiotherapy and immunotherapy, which assists personalized treatment optimization in LUAD.